ATTITUDE OF ANESTHESIOLOGY SPECIALISTS AND RESIDENTS TOWARDS PATIENTS INFECTED WITH THE NOVEL CORONAVIRUS (COVID 19) IN TERTIARY CARE HOSPITALS OF KARACHI (The Research of Medical Science Review, 2025)
OBJECTIVE: To assess the attitude of anesthesiologists towards airway management in COVID 19 patients. METHODOLOGY: This cross-sectional research is scheduled for execution in 2024 within the Anaesthesiology Department of the Indus Hospital, Karachi, with an enrollment of 157 anesthesiologists. Eligible participants were anesthesia residents and specialists who worked in tertiary care hospitals, aged 20-70 years, of either gender, to assess the assess their attitude towards airway management in COVID 19 patients. Data will be entered and analyzed by SPSS version 26. escriptive statistical analyses were conducted, and the data underwent rigorous examination to produce results with a confidence interval of 95%. RESULTS: The investigation encompassed a cohort of 157 anesthesiologists, exhibiting a mean age of 35.24± 6.98 years; male participants constituted 54.1% of the sample, while female participants represented 45.9%. A considerable proportion of the participants possessed less than five years of professional experience and were employed in private healthcare institutions. Although 66.9% indicated the presence of formal COVID-19 protocols, merely 46.5% had undergone training in airway management. Attitudinal responses exhibited significant variability in relation to gender, type of hospital, training received, and the availability of protocols, with 87.9% demonstrating a favorable disposition towards airway management concerning COVID-19. CONCLUSION: The majority of anesthesiologists in tertiary hospitals located in Karachi exhibited an affirmative disposition towards the management of patients afflicted with COVID-19, particularly in relation to airway management. Nevertheless, those practitioners possessing formal training or employed within public healthcare facilities demonstrated an increased likelihood of expressing apprehensions—potentially attributable to an elevated awareness of risk factors. These findings underscore the necessity for educational initiatives that enhance both competencies and self-efficacy, in conjunction with improved institutional support mechanisms.